(untitled) (Journal of Mathematics Mechanics and Computer Science, 2018)
The behavior thermocouple in a solid medium is an interesting opportunity problem for accuracy of temperature measurement.This work considers interaction of thermocouple embedded in the solid substance pyrolyzed by external heat source with heat wave propagating inside the substance from the surface of its pyrolysis. Numerical simulation has shown that significant difference in the values of thermal conductivity coefficients of solid substance and thermocouple material results in the heat flow along thermocouple wires inside the substance that substantially changes thermo junction temperature thus misrepresenting thermocouple data.